Comprehensive description of adult-onset Still's disease after COVID-19 vaccination. Issue 134 (January 2023) - Palassin, Pascale; Bres, Virginie; Hassan, Samaher; Alfonsi, Ange; Massy, Nathalie; Gras-Champel, Valérie; Maria, Alexandre Thibault Jacques; Faillie, Jean-Luc; ,
Abstract: Cases of adult-onset Still's disease (AOSD) have been reported after COVID-19 vaccination. Here we provide a comprehensive description and analysis of all cases of AOSD reported in the literature and in pharmacovigilance databases through April 2022. Disproportionality analyses of pharmacovigilance data were performed in order to further explore the association between vaccination and AOSD. We included 159 patients, 144 from the World Health Organization pharmacovigilance database and 15 from the literature. Detailed clinical characteristics were described for the cases from the literature and from the French pharmacovigilance database (n = 9). The cases of AOSD after COVID-19 vaccination concerned women in 52.2% of cases. The median age was 43.4 years. More than 80% of AOSD reports occurred during the first three weeks and concerned mostly the BNT162b2 mRNA vaccine. We identified 14.5% of disease flare with a median time-to-onset of AOSD flare-up significantly shorter than for the new onset form. More than 90% patients received steroids. Although all cases were considered serious and required hospitalization, most cases presented a favorable outcome (67.1%) with a good response to corticosteroid therapy with a mean time to recovery of 7.2 days. Disproportionality analyses suggested that AOSD was associated with COVID-19 vaccines as well as other vaccines. AOSD was nearly five times more frequently reported with COVID-19 vaccines than with all other drugs. Clinicians should be informed about the potential risk of AOSD onset or flare following COVID vaccines and the importance of its early detection to optimize its management. Highlights: Cases of AOSD after COVID-19 vaccination have been reported in literature and to the pharmacovigilance systems. We provide the largest series and a comprehensive description in order to better characterize this adverse drug reaction. Disproportionality showed that AOSD is five times more frequently reported with COVID-19 vaccines than with other drugs. Time to onset is significantly shorter in flares compared to new onset disease. Clinicians should be aware of this potential serious adverse drug reaction.